2005
DOI: 10.2527/2005.83122863x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer sensory acceptance and value of domestic, Canadian, and Australian grass-fed beef steaks1

Abstract: To determine US consumer acceptance and value of beef from various countries, 24 taste panels of consumers (n = 273 consumers) were conducted in Denver and Chicago. Two pairs of strip steaks were evaluated for flavor, juiciness, tenderness, and overall acceptability on eight-point hedonic scales. One pair consisted of an Australian grass-fed strip steak and a domestic strip steak, whereas the other pair included Canadian and domestic strip steaks. The pairs were matched to similar Warner-Bratzler shear values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 13 publications
11
84
2
Order By: Relevance
“…These results align with previous reports that U.S. consumers were willing to pay more for domestic U.S. grain finished beef when compared to imported beef from countries such as Australia, Canada, and Argentina, where finishing practices differ from those in the U.S. (Killinger et al, 2004;Sitz et al, 2005). Killinger et al (2004) found that U.S. consumers were willing to pay more for U.S. beef compared to grassfed Argentine beef, and they were willing to pay even more when they found domestic samples more acceptable than Argentine steaks.…”
Section: Willingness To Paysupporting
confidence: 91%
See 2 more Smart Citations
“…These results align with previous reports that U.S. consumers were willing to pay more for domestic U.S. grain finished beef when compared to imported beef from countries such as Australia, Canada, and Argentina, where finishing practices differ from those in the U.S. (Killinger et al, 2004;Sitz et al, 2005). Killinger et al (2004) found that U.S. consumers were willing to pay more for U.S. beef compared to grassfed Argentine beef, and they were willing to pay even more when they found domestic samples more acceptable than Argentine steaks.…”
Section: Willingness To Paysupporting
confidence: 91%
“…Even when Sitz et al (2005) matched U.S. strip steaks to either Canadian or Australian grass-fed strip steaks according to similar Warner-Bratzler shear force values and marbling, U.S. consumers were accustomed to U.S. domestic beef flavor and preferred that over either imported option, which aligned with the current results. Honduran consumers, however, did not show allegiance to their domestic product, rating both U.S. treatments greater for overall liking than either of the Honduran treatments.…”
Section: Consumer Ratings and Acceptabilitysupporting
confidence: 81%
See 1 more Smart Citation
“…While it has been known for many years that tenderness and juiciness play a large role in acceptability of meat by a consumer, it has become increasingly apparent that flavour also needs to be addressed. In a large, multiple-city study, flavour was found to be the most important factor affecting consumers' meat buying habits and preferences when tenderness was held constant (Sitz et al, 2005). Similar results were received in a study of Jaworska et al (2006).…”
Section: Discussionsupporting
confidence: 79%
“…Generally, consumers prefer to have high quality, convenient and safe meat products that contain natural flavour and taste (Aymerich et al, 2008). Flavour, which comprises mainly the two sensations of taste and aroma or smell, has been found to be one of the most important factors affecting consumers' meat-buying habits and preferences even before the meat is eaten (Shahidi, 1989;Sitz et al, 2005). Of all types of meat consumed in the world, chicken continues to be the cheapest, and its consumption is expected to increase by 34% by 2018 (Jung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%